2023
DOI: 10.3389/fphar.2023.1164309
|View full text |Cite
|
Sign up to set email alerts
|

The safety concerns regarding immune checkpoint inhibitors in liver cancer patients rising mainly from CHB

Abstract: Aim: To analyze the safety of immune checkpoint inhibitors in primary liver cancer patients and to identify the risk factors for immune-related adverse events (irAEs).Methods: The study enrolled 106 patients with primary liver cancer, including 81 with hepatocellular carcinoma and 25 with intrahepatic cholangiocarcinoma. We analyzed the differences between groups in irAE occurrence, including those with and without targeted drugs and those who received interventional therapy.Results: The incidence of irAEs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…The median age at the onset of ICI-DM was determined to be 61 years ( 36 ). The combination therapy resulted in an increased risk of immune-related DM compared to a single one ( 37 ). The mean time of onset of ICI-DM was 8.14 weeks (full range, 3.6-45 weeks) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The median age at the onset of ICI-DM was determined to be 61 years ( 36 ). The combination therapy resulted in an increased risk of immune-related DM compared to a single one ( 37 ). The mean time of onset of ICI-DM was 8.14 weeks (full range, 3.6-45 weeks) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Host immunity plays a critical role in the pathogenesis of malignancies, as evidenced by the early successes of immune checkpoint blockade therapy (4) in reactivating compromised host immune responses. However, the application of immune checkpoint blockade in HCC patients has been associated with serious adverse reactions (5,6), including severe hepatic damage (7). Consequently, gaining a better understanding of the underlying mechanisms involved in HCC development is imperative for designing personalized precision medicine approaches that can mitigate these adverse effects and improve patient outcomes.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…The introduction of anti-PD-1/PD-L1 therapies has heralded a paradigm shift in cancer treatment, presenting markedly improved outcomes for patients who would otherwise confront more severe conditions ( 10 ). Nevertheless, a notable proportion of adverse effects has been observed in cancer patients following anti-PD-1 therapy ( 11 ). For instance, our previous research demonstrated serious adverse responses in hepatocellular carcinoma patients in response to ICIs ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a notable proportion of adverse effects has been observed in cancer patients following anti-PD-1 therapy ( 11 ). For instance, our previous research demonstrated serious adverse responses in hepatocellular carcinoma patients in response to ICIs ( 11 ).…”
Section: Introductionmentioning
confidence: 99%